Obesity trends and determinant factors in Latin America Tendencias en la obesidad y factores determinantes en América Latina - Juliana Kain; Fernando Vio; Cecilia Albala (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2003)
Obesity rates have increased markedly in Latin America, especially during the last 10-15 years, becoming a public health problem in most countries. Prevalence of obesity among preschool children remains low, while among schoolchildren it has increased considerably. Prevalence is high in the adult population, especially among women with less schooling. In developed populations, obesity occurs more frequently among the poor; the opposite occurs in less developed societies, where in households undergoing nutritional transition, underweight can coexist with obesity. The most important determinant factors involved in the increasing obesity prevalence are fetal and infant nutritional conditions (stunting), education and socioeconomic conditions, dietary changes (especially increased total energy intake), and physical inactivity. Because chronic diseases are the main causes of death in the Region and obesity is one of the main risk factors for these diseases, policies to improve economic and educational levels with the implementation of health promotion and prevention should be a priority in every country. En América Latina la obesidad ha aumentado considerablemente llegando a convertirse en un problema de salud pública en casi todos los países. La prevalencia de obesidad es baja entre los preescolares, pero ha aumentado significativamente entre los escolares. En los adultos, la prevalencia es alta, especialmente entre las mujeres con menor educación. En sociedades más desarrolladas, la obesidad aparece más frecuentemente entre los pobres, lo opuesto ocurre en poblaciones pobres, donde, además, puede coexistir la desnutrición junto a la obesidad. Los factores de riesgo más importantes relacionados con el incremento de la obesidad son: las condiciones fetales y la situación nutricional durante la infancia (talla baja), características socioeconómicas y nivel educacional, aspectos dietéticos y la inactividad física. Por ello, y debido a que las enfermedades crónicas constituyen la principal causa de muerte en todos los países de la región, y la obesidad es uno de los principales factores de riesgo de éstas, la implementación de políticas y programas que apunten mejorar la situación económica y educacional de los más pobres y al mismo tiempo cambiar los hábitos de vida de toda la población es absolutamente prioritario.